Hypothalamic peptidyl-glycine alpha-amidating monooxygenase: preliminary characterization - Emeson, RB (J Neurosci, 1984)
An enzymatic activity capable of converting mono-[125I]-D-Tyr-Val-Gly into mono-[125I]-D-Tyr-Val-NH2 was identified in a crude mitochondrial/synaptosomal preparation from rat hypothalamus. Further subcellular fractionation studies localized a majority of this enzymatic activity to fractions enriched in synaptic vesicles. The alpha-amidation activity demonstrated optimal activity at pH 7.5 to 8, was stimulated by the presence of copper ions and reduced ascorbate and required the presence of molecular oxygen. Endogenous alpha-amidation activity was inhibited by the addition of ascorbate oxidase. Kinetic analyses demonstrated Michaelis-Menten type kinetics for D-Tyr-Val-Gly as the varied substrate with the values of Km and Vmax increasing as the ascorbate concentration in the reaction increased. A variety of peptides possessing carboxyl-terminal glycine residues were potent inhibitors of the reaction, while peptides lacking a carboxyl-terminal glycine residue were not, suggesting that many glycine-extended peptides may serve as substrates in the alpha-amidation reaction. The characteristics of hypothalamic alpha-amidation activity are similar to those previously reported for the alpha-amidation activity in rat pituitary and mouse corticotropic tumor cells suggesting the presence of closely related enzymes in these tissues.